Direct evidence for bulk photovoltaic charge transport in a ferroelectric polycrystalline film. (1st April 2022) - Blázquez Martínez, Alfredo; Grysan, Patrick; Girod, Stéphanie; Glinsek, Sebastjan; Granzow, Torsten
Abstract: The anomalous or bulk photovoltaic (BPV) effect in ferroelectrics is not subject to the Shockley-Queisser limit capping the efficiency of interface-based semiconductor photovoltaics. Therefore, it has been widely explored for applications in photovoltaic energy harvesters, non-destructive read-out mechanisms for data storage, or photorefractive thin-film devices. However, all investigations have so far been restricted to single crystals and epitaxial thin films; there is yet no direct evidence of a bulk photovoltaic charge transport in polycrystalline thin films, which would open a much larger range of economical applications. This study demonstrates the bulk nature of the photovoltaic effect in polycrystalline solution-processed BiFeO3 thin films. A light-polarization-dependent photocurrent is shown. Combined with the dependence of the photocurrent on the poling state of the film and the light intensity, as well as the scaling of open-circuit voltage with electrode distance, this clearly indicates that the charge carrier separation relies on the BPV effect. Graphical abstract: Image, graphical abstract